On Skew Left n-Derivations with Lie Ideal Structure (Baghdad Science Journal, 2019)
In this paper the centralizing and commuting concerning skew left -derivations and skew left -derivations associated with antiautomorphism on prime and semiprime rings were studied and the commutativity of Lie ideal under certain conditions were proved.